Ballistic Performance Anti-Projectile Of Alumina And Weldox 460 E with Finite Element Method - Pratiwi, Dessy Ade; Riyadi, Tri Widodo Besar; Setiadhi, David; Hariyanto, Agus (Creative Research in Engineering (CERIE), 2023)
This research aims to determine the effect of the panel configuration which has the strongest resistance and to analyze the ballistic toughness of the Al2O3 and Weldox 460 E Steel panel configurations. The criteria to be looked for are the Depth of Penetration, Deflection and Final Projectile Length. To determine the accuracy of this study, a verification of the simulation research previously conducted by Dey et al. The method used is based on simulation with the finite element method. The software used is ANSYS/Explicit Dynamic solver AUTODYN 18.1. The modeling used in this study is simplified into 2D Axisymmetric. Alumina and Weldox 460 E steel panel configuration variations that will be used in this study. There are 7 variations of the panel configuration used, namely B12, A5B5, A5B10, A10B5, A10B10, A12B12 and A15B15. Alumina material as the front panel, while Weldox 460 E as the back panel. In calculating the mechanical behavior of the material, while the Alumina material uses the Johnson Holmquist (JH2) Strength parameter. And then, the Weldox 460 E material uses Johnson and Cook parameters. The results obtained indicate that the A12B12 and A15B15 panel configurations are able to withstand projectiles. The A12B12 panel configuration has a depth of penetration value of 23 mm, a deflection value of 4.3 mm and a Vbl value of 954.69 m/s. while the best panel configuration is A15B15 with a depth of penetration value of 21 mm, a deflection value of 1.4 mm and a Vbl value of 1345.9 m/s. then the conclusion of this study shows that the A15B15 panel configuration is the best panel configuration that is able to withstand projectiles.